Synthesis and Antimicrobial Activity of Short Analogues of the Marine Antimicrobial Peptide Turgencin A: Effects of SAR Optimizations, Cys-Cys Cyclization and Lipopeptide Modifications - Dey, Hymonti; Simonovic, Danijela; Hagen, Ingrid Sofie Norberg-Schulz; Vasskog, Terje; Fredheim, Elizabeth G. Aarag; Blencke, Hans-Matti; Anderssen, Trude; Strøm, Morten B.; Haug, Tor (International Journal of Molecular Sciences, 2022)
We have synthesised short analogues of the marine antimicrobial peptide Turgencin A from the colonial Arctic ascidian Synoicum turgens. In this study, we focused on a central, cationic 12-residue Cys-Cys loop region within the sequence. Modified (tryptophan- and arginine-enriched) linear peptides were compared with Cys-Cys cyclic derivatives, and both linear and Cys-cyclic peptides were N-terminally acylated with octanoic acid (C 8 ), decanoic acid (C 10 ) or dodecanoic acid (C 12 ). The highest antimicrobial potency was achieved by introducing dodecanoic acid to a cyclic Turgencin A analogue with low intrinsic hydrophobicity, and by introducing octanoic acid to a cyclic analogue displaying a higher intrinsic hydrophobicity. Among all tested synthetic Turgencin A lipopeptide analogues, the most promising candidates regarding both antimicrobial and haemolytic activity were C 12 -cTurg-1 and C 8 -cTurg-2. These optimized cyclic lipopeptides displayed minimum inhibitory concentrations of 4 µg/mL against Staphylococcus aureus, Escherichia coli and the fungus Rhodothorula sp. Mode of action studies on bacteria showed a rapid membrane disruption and bactericidal effect of the cyclic lipopeptides. Haemolytic activity against human erythrocytes was low, indicating favorable selective targeting of bacterial cells.